1999
DOI: 10.1093/alcalc/34.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Does the concept of a standard drink apply to viticultural societies?

Abstract: The use of standard drink units (SDUs) in the measurement of individual alcohol consumption has become widely popular in recent years. However, the ethanol content of drinks varies from country to country and is usually arrived at without scientific backing. The present study was designed to establish an SDU for a predominantly wine-drinking country (Spain). Two field studies were simultaneously conducted to gather data about home and public alcohol consumption in eight regions of the country with a total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 0 publications
1
71
0
Order By: Relevance
“…– Alcohol consumption, registered as the weekly number of drinking units (a glass of wine, a bottle of beer or a drink of spirits), approximately equivalent to 10 g of alcohol [25]. …”
Section: Methodsmentioning
confidence: 99%
“…– Alcohol consumption, registered as the weekly number of drinking units (a glass of wine, a bottle of beer or a drink of spirits), approximately equivalent to 10 g of alcohol [25]. …”
Section: Methodsmentioning
confidence: 99%
“…The calculation of alcohol use was made using the 'Standard Drink Unit'. In Spain, the SDU is equivalent to 10 g of pure alcohol [10]. Average amount of alcohol consumed per week by subjects completing the treatment (3.36 units) was significantly lower than that of non-completers (5.45 units) (p !…”
Section: Comparison Of Completion/drop-outmentioning
confidence: 97%
“…Some studies have shown respondents pictures of containers and glasses with pour levels marked with letters rather than volume labels and asked them to find the closest matching vessel and pour level, or in faceto-face situations, to solicit responses using actual glassware with labeled pour levels [153]. Other strategies include having respondents pour a drink like their usual one into glasses provided to estimate their usual pour [162,163] or to have them attempt to pour a standard drink into provided glasses to gauge their ability to do so [164,165]. Finally, direct measurement of simulated usual drinks poured at home is the method that we believe is most accurate for use in any survey mode where respondents are contacted in their own home (and a large proportion of drinking is in home settings-not always the case).…”
Section: Home Drink Measurement Strategiesmentioning
confidence: 99%
“…To measure mixed drinks two strategies have been used. A Spanish study [162] determined popular drinks in each bar through observation of patrons and then worked with the bartender to measure each ingredient as an example of how each popular drink was made. One issue with this strategy is that the bartenders are aware of the measurement activity and may make the drink differently than they would otherwise.…”
Section: On-premise Drink Measurement Strategiesmentioning
confidence: 99%